A new 3D 3-fold interpenetrated framework from flexible tricarboxylate: Photocatalytic and sensing performances. (15th November 2021) - Zhou, Shanhe; Wang, Jun; Liu, Dong; Cai, Shulan; Guo, Junru; Panc, Ying; Zheng, Rouqiao; Muddassir, Mohd.; Sakiyama, Hiroshi
Graphical abstract: Abstract: A new metal–organic framework of [Zn2 (HL)2 (4, 4′-bipy)]·3H2 On (1 ) (H3 L = 1, 3, 5-tris(4-carbonylphenyloxy)benzene, 4, 4′-bipy = 4, 4′-bipyridine), was hydrothermally prepared and full characterized. 1 possesses 3D 3-fold interpenetrated framework. 1 obtained effectively photocatalytic performance to the disintegration of dyes Rhodamine B (Rh B) and methylene blue (MB). Furthermore, MOF 1 was selected as a selective probe for antibiotics metronidazole (MDZ) having the low detection limit 1.16 ppm. The plausible mechanism displayed by 1 for the catalytic degradation toward Rh B was proposed using the trapping method and LC-MS studies.